Tissue-Specific Metabolic Regulation of FOXO-Binding Protein: FOXO Does Not Act Alone - Noriko Kodani; Jun Nakae (Cells, 2020)
The transcription factor forkhead box (FOXO) controls important biological responses, including proliferation, apoptosis, differentiation, metabolism, and oxidative stress resistance. The transcriptional activity of FOXO is tightly regulated in a variety of cellular processes. FOXO can convert the external stimuli of insulin, growth factors, nutrients, cytokines, and oxidative stress into cell-specific biological responses by regulating the transcriptional activity of target genes. However, how a single transcription factor regulates a large set of target genes in various tissues in response to a variety of external stimuli remains to be clarified. Evidence indicates that FOXO-binding proteins synergistically function to achieve tightly controlled processes. Here, we review the elaborate mechanism of FOXO-binding proteins, focusing on adipogenesis, glucose homeostasis, and other metabolic regulations in order to deepen our understanding and to identify a novel therapeutic target for the prevention and treatment of metabolic disorders.